A review of the effectiveness of guided notes: can it support students’ note taking in mathematics lecture? / Muniroh Hamat ... [et al.] - Hamat, Muniroh; Mahlan, Siti Balqis; Shamsuddin, Maisurah; Umar, Norazah (Unit Penerbitan JSKM, 2025)
Guided notes are essentially teacher-prepared handouts that help students take more effective notes during a lesson or lecture. Guided notes can be used in a variety of subjects and for students of all ages. They are particularly helpful for students who struggle with notetaking or have learning disabilities. Guided notes, which include pre-prepared handouts with essential concepts and partially finished examples, are expected to boost student engagement and comprehension when compared to typical note-taking approaches. The study examines the benefits and effects of guided notes on students' strategies for taking notes in class, their ability to recognise and document key information, and their subsequent exam performance. Additionally, this study assesses the value of guided notes as a teaching tool in college-level mathematics courses and offers suggestions for how to use them to enhance student learning.